(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The article describes the process of obtaining nickel from waste GIAP-8 and similar catalysts, which are used in the form of nickel nitrate, which is considered not only environmentally friendly, but also an economically viable solution for its production. Nickel catalysts isolated from waste were tested in laboratory conditions and used in production.